Analisis Strategi Pertahanan Indonesia dalam Rangka Pengamanan Selat Makassar (2019-2024) - Al-Ghifari, Muhammad Dzimar; Wiswayana, Wishnu Mahendra (Syntax Corporation, 2025)
The Makassar Strait is an Indonesian maritime territory that has an important function not only for Indonesia, but also for other countries that use the Makassar Strait as their sea transportation route. The urgency of the security of the Makassar Strait itself is also driven by the plan to move the Indonesian Capital City to the Nusantara Capital City in East Kalimantan, more precisely in the Penajam Paser Utara Regency and Kutai Kartanegara Regency. This study will use the concept of maritime security according to Chris Rahman as the basis for research on Indonesia's strategy in securing the Makassar Strait. By using qualitative research methods, the author will focus on collecting data through literature studies, to answer the research question